ОБЗОР ПРОГРАММНЫХ ПРОДУКТОВ ДЛЯ ОБРАБОТКИ ДАННЫХ ОРНИТОЛОГИЧЕСКОГО МОНИТОРИНГА - Matsyura, A V; Jankowski, K (Acta biologica Sibirica, 2016)
A review of the most common computer programs for processing data ornithological monitoring. The possibilities and limitations of programs, examples of their use. The technique of field data processing with the help of environmental applications of computer programs.